2023
DOI: 10.1051/0004-6361/202244534
|View full text |Cite
|
Sign up to set email alerts
|

Holismokes

Abstract: Modeling of strongly gravitationally lensed galaxies is often required in order to use them as astrophysical or cosmological probes. With current and upcoming wide-field imaging surveys, the number of detected lenses is increasing significantly such that automated and fast modeling procedures for ground-based data are urgently needed. This is especially pertinent to short-lived lensed transients in order to plan follow-up observations. Therefore, we present in a companion paper a neural network predicting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 124 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…Over the recent years, deep-learning methods have proven extremely successful at accurately modeling strong lensing systems (Hezaveh et al 2017;Perreault-Levasseur et al 2017;Morningstar et al 2018;Coogan et al 2020;Legin et al 2021;Park et al 2021;Wagner-Carena et al 2021;Anau Montel et al 2022;Karchev et al 2022;Legin et al 2022;Mishra-Sharma & Yang 2022;Schmidt et al 2023;Schuldt et al 2023;Wagner-Carena et al 2023). More specifically, Morningstar et al (2019) demonstrated that recurrent convolutional neural networks can implicitly learn complex prior distributions from their training data to reconstruct pixelated undistorted images of strongly lensed sources successfully, circumventing the need to specify explicitly a prior distribution over those parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Over the recent years, deep-learning methods have proven extremely successful at accurately modeling strong lensing systems (Hezaveh et al 2017;Perreault-Levasseur et al 2017;Morningstar et al 2018;Coogan et al 2020;Legin et al 2021;Park et al 2021;Wagner-Carena et al 2021;Anau Montel et al 2022;Karchev et al 2022;Legin et al 2022;Mishra-Sharma & Yang 2022;Schmidt et al 2023;Schuldt et al 2023;Wagner-Carena et al 2023). More specifically, Morningstar et al (2019) demonstrated that recurrent convolutional neural networks can implicitly learn complex prior distributions from their training data to reconstruct pixelated undistorted images of strongly lensed sources successfully, circumventing the need to specify explicitly a prior distribution over those parameters.…”
Section: Introductionmentioning
confidence: 99%